(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Microfinance focuses on economic development at a minute level. Microfinance is adopted to reduce the poverty level in the economic system. This study is conducted to investigate the microfinance institutions’ outreach, its growth Microfinance is a category of financial services targeting individuals and small businesses that lack access to conventional banking and related services,. Microfinance Institutions’ long-term viability is under doubt. An all-out effort is needed to assist build the embryonic Microfinance Industry while addressing the trade-off between outreach and sustainability. Financial services in rural areas and long-term national financial development are used to examine this problem in detail. The study which discussed about, need of microfinance, Microfinance institution-presence in rural sectors, Microfinance and financial inclusion-two important dimensions of rural financing, Rural financing scenario in Maharashtra with special reference to microfinance and financial inclusion, Data analysis of micro financial institutions client’s responses, Informal financial organisations and rural financing in Maharashtra with special reference to microfinance ,Impact of microfinance services on poverty alleviation